DOI: 10.22215/etd/2018-12624
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Signal Quality of Wrist-Based Photoplethysmography

Abstract: Detection of paroxysmal atrial fibrillation requires continuous cardiovascular monitoring due to its episodic nature. Such monitoring is impractical with electrocardiogram Holter monitors, which are the currently employed for ambulatory cardiovascular monitoring, but are cumbersome for prolonged use. This thesis studies monitoring using photoplethysmography (PPG) devices, which may be embedded into wristband devices which can be easily worn continuously. However, the quality of wrist-based PPG is highly variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The features used were the values at the first two peaks in the correlogram. These features were inspired by Wander and Morris (2014), and previously used in preliminary work done by our research team (Pradhan 2017). • Median noise ratio per pulse: This feature is the median of the signal-to-noise ratio (SNR) computed from each pulse in the PPG segment.…”
Section: • Number Of Zero-crossingsmentioning
confidence: 99%
“…The features used were the values at the first two peaks in the correlogram. These features were inspired by Wander and Morris (2014), and previously used in preliminary work done by our research team (Pradhan 2017). • Median noise ratio per pulse: This feature is the median of the signal-to-noise ratio (SNR) computed from each pulse in the PPG segment.…”
Section: • Number Of Zero-crossingsmentioning
confidence: 99%
“…The use of PPG is limited because of its high sensitivity to motion. One study assessed the quality of the PPG signals using the Empatica E4 wristband and found that around 35% of data are considered high quality, that is, having “all identifiable pulses,” and this quality improves appreciably during sleep, when motion is less likely 20 . PPG signals may also be affected by orthostatic changes 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, PPG‐based heart rate from wrist‐worn devices can be reliably used for monitoring when hand movements are limited, 35 and signals can be further cleaned to remove artifacts and improve cardiovascular monitoring 20,36 . Our samples included patients mostly in awake state (69%), and >95% of our signals had good quality (62% had fully identifiable pulses on the PPG signal, and another 33% had identifiable pulses for >75% of the portions 20 ). More than 69% of the signals had a completely flat accelerometry signal with no major orthostatic variations, as patients were in bed for the majority of the recording.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation